Melhoria do processo para localização física dos materiais informacionais nos acervos das bibliotecas: o caso da biblioteca do Centro de Ciências Humanas da Universidade Federal do Maranhão - BELFORT, Amanda Rocha (2024)
This research has the general objective of developing an improvement to the physical location process of information materials in the library collection of the Center for Human Sciences (CCH) of the Federal University of Maranhão (UFMA), through a technological solution that will demonstrate the location of shelf of the desired material. In libraries that have a vast collection, being able to locate a book on the shelves is not always a simple and quick task, either due to the size of the collection or not knowing how information materials are arranged and ordered. The methodology adopted, from the point of view of its procedures, is a case study, having as its location the UFMA CCH Library, in terms of its nature; applied and technological, mixed in relation to the approach, exploratory from the point of view of its objectives and bibliographical research and survey regarding the technical procedures used. A bibliographical review was carried out on the CAPES portal in order to understand the theme of the proposal. A mapping of the libraries of federal universities in Brazil was carried out in order to identify which libraries provided the functionality for locating information materials in the online catalog. The results obtained were: among the 37 systems that use the Pergamum software, 18 have the functionality, even if inactive. Within this group, only 2 libraries have this functionality working; Of the 15 institutions that use SIGAA, none provide this functionality. Furthermore, the development of the improvement was carried out with the customization of the SIGAA screens and, finally, the improvement instruction manual was prepared for users and librarians.